Analisis Penentuan Kebijakan Struktur Modal pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia tahun 2005 - 2008 - Indah, Nopiani (MABIS, 2011)
This study aimed to test whether leverage was influenced by asset tangibility, profitability, growth, non-debt tax shield, the cash holding and firm size. In addition, this study also aimed to test whether the pecking order theory or Static Trade Off Theory in effect on the mining company listed on the Stock Exchange in the year 2005-2008. This study uses causal research. Sample of research using non-probability sampling with a purposive sampling technique, in order to obtain a sample of seven companies with a four-year study period = 28 samples. Based on the results of multiple regression analysis with the F test, coefficient of determination (R square) shows the change of independent variables (asset tangibility, profitability, growth, non-debt tax shields, cash holding and firm size) are only able to explain changes in the dependent variable (leverage) at 42,8% (have a significant effect on leverage). While the rest equal to 57,2% explained by other factors not included in the regression model. Based on the results of T test showed that the variables are variables having significant influence of growth coefficient of 0,655 and significant value of 0,018. While other independent variables (asset tangibility, profitability, non-debt tax shields, cash holding and firm size) the significant value of more than 5% (not significant). Mining companies in Indonesia are more likely to follow the pecking order theory (POT) in establishing the companys funding decisions. This is realized by Attribute asset tangibility, profitability, growth, cash holding and firm size have the influence to leverage the company and support the hypothesis POT in determining funding decisions for mining companies in Indonesia Stock Exchange.